PENARIKAN KEMBALI HARTA BERUPA TANAH YANG TELAH DIWAKAFKAN MENURUT HUKUM ISLAM (Studi Kasus Putusan Nomor : 1/Pdt.G/2011/PTA.Smd) - Ahmad Ramadani (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTThe research on withdrawal of assets such as land that has been in the endowment according to Islamic law (Case Study verdict numbers: 1 / Pdt.G / 2011 / PTA.Smd),  is motivated by legal act of someone who donating property such as land based on Islamic Law Compilation (ILC) and Law Number 41 Year 2004 about waqf which basically waqf deed is person or group of persons or legal entities to separate and/or submit most of his possessions to be used forever or for a certain periode of time in accordance with its interests for religious purposes. However the land which has been in endowment can be made possible to withdrawn by the parties especially wakif or the heirs of wakif.By this author discusses about whether the donated land may be withdrawn in accordance with Islamic law and legislation on waqf. How the Law on waqf can allow the withdrawal of donated land, How alignment of factors into consideration the judge against the Act of  waqf in dropping Decision Number 1/Pdt.G/2011/PTA.Smd.In this study the authors used a qualitative research using normative juridical approach. This is a source of research data in the form of the Decision Document Number 1/Pdt.G/2011/PTA.Smd., Literary study of books and scientific articles on waqf land, Interviews with young clerk of law, Interview with young clerk of lawsuit and Religious Court judges, Waqf deed official pledge sub-district sungai kunjang dan Registration Section of the Office of Land Rights Samarinda. The results showed that the withdrawal of assets such as land which has be donated land can be done if the implementation of waqf endowments are not eligible and pillars of endowments listed in Article 6 of Law Number 41 Year 2004 about waqf. In Decisions Number 1/Pdt.G/2011/PTA.Smd, waqf are distributed according to the value of the price. The alignment of factors into consideration judges with legislation waqf in dropping Decision Number 1/pdt.G/2011/PTA.Smd is right. Keywords: Islamic Law,Waqf land, Assets